Extracellular cleavage and shedding of P-cadherin: a mechanism underlying the invasive behaviour of breast cancer cells - Ribeiro, A. S. (2010)
Cell-cell adhesion is an elementary process in normal epithelial cellular architecture. Several studies have shown the role mediated by cadherins in this process, besides their role in the maintenance of cell polarity, differentiation and cell growth. However, during tumour progression, these molecules are frequently altered. In breast cancer, tumours that overexpress P-cadherin usually present a high histological grade, show decreased cell polarity and are associated with worse patient survival. However, little is known about how this protein dictates the very aggressive behaviour of these tumours. To achieve this goal, we set up two breast cancer cell models, where P-cadherin expression was differently modulated and analysed in terms of cell invasion, motility and migration. We show that P-cadherin overexpression, in breast cancer cells with wild-type E-cadherin, promotes cell invasion, motility and migration. Moreover, we found that the overexpression of P-cadherin induces the secretion of matrix metalloproteases, specifically MMP-1 and MMP-2, which then lead to P-cadherin ectodomain cleavage. Further, we showed that soluble P-cadherin fragment is able to induce in vitro invasion of breast cancer cells. Overall, our results contribute to elucidate the mechanism underlying the invasive behaviour of P-cadherin expressing breast tumours.